2022
DOI: 10.3389/fimmu.2022.832106
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and Evolution of Antigenic Determinants of SARS-CoV-2: An Insight for Immune Escape and Vaccine Design

Abstract: Coronavirus disease 2019 (COVID-19) is the most devastating pandemic of the century, which is still far from over. The remarkable success of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines is the working hope, but the evolving variants are the huge concern that can turn the tide. Potential immune escape mutations (PIEMs) in the past and circulating variants were not studied at large scale (all available data). Hence, the conservation of antigenic determinants (epitopes) was analyzed in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Jaiswal et al mathematically (in-house developed PERL scripts) revealed sets of epitopes on the S1 subunit around 453 to 538 that interact with the ACE and are 99% conserved among the variants of SARS-CoV-2 [ 116 ]. Their study further identified conserved common neutralizing epitopes on the SARS-CoV-2, including YLTPGDSSSGWTAGAAAYYV (247–267 aa), TFKCYGVSPTKLNDL (376–390 aa) on S1 and LNEVAKNLNESLIDLQELGK (1186–1205 aa) on the S2 [ 116 ].…”
Section: Sars-cov-2 S Conserved Regions As a Potential Target For Vac...mentioning
confidence: 99%
“…Jaiswal et al mathematically (in-house developed PERL scripts) revealed sets of epitopes on the S1 subunit around 453 to 538 that interact with the ACE and are 99% conserved among the variants of SARS-CoV-2 [ 116 ]. Their study further identified conserved common neutralizing epitopes on the SARS-CoV-2, including YLTPGDSSSGWTAGAAAYYV (247–267 aa), TFKCYGVSPTKLNDL (376–390 aa) on S1 and LNEVAKNLNESLIDLQELGK (1186–1205 aa) on the S2 [ 116 ].…”
Section: Sars-cov-2 S Conserved Regions As a Potential Target For Vac...mentioning
confidence: 99%
“…Considering the ineffectiveness of current SARS-CoV-2 antibody-based immunotherapy due to the development of novel mutations and the immune escape of the VOCs ( 52 ), other therapeutic options are warranted. Adoptive SARS-CoV-2 specific T cell therapy represents an attractive therapeutic option in which viral immune escape is likely to be avoided as the recognized T cell epitopes are well conserved among the emerging SARS-CoV-2 variants ( 25 ). Moreover, adoptive cellular therapy with ex-vivo expanded specific T cells against other viruses (CMV, EBV, Adv, HHV6, and BKV) has been demonstrated to have efficacy in combating severe viral diseases in patients with immunodeficiency ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that T cell memory response in COVID-19 vaccinated, and convalescent individuals could be more persistent than antibody response leading to a more durable source of protection ( 23 , 24 ). Furthermore, recent studies indicated that T cell response and functionality against SARS-CoV-2 were not affected by the mutations or antigenic variation of the emerging variants of concern as the humoral response ( 25 27 ). These findings provide direct evidence that a lack or impairment of the T cell response could be associated with an elevated risk of SARS-CoV-2 infection and severe COVID-19 disease outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Jaiswal et al mathematically (in-house developed PERL scripts) revealed sets of epitopes on the S1 subunit around 453 to 538 that interact with the ACE are 99% conserved among the variants of SARS-CoV-2 [106]. Their study further identified conserved common neutralizing epitopes on the SARS-CoV-2 including YLTPGDSSSGWTAGAAAYYV (247-267 aa), TFKCYGVSPTKLNDL (376-390 aa) on S1 and LNEVAKNLNESLID-LQELGK (1186-1205 aa) on the S2 [106].…”
Section: Sars-cov-2 S Conserved Regions As a Potential Target For Vac...mentioning
confidence: 99%
“…Jaiswal et al mathematically (in-house developed PERL scripts) revealed sets of epitopes on the S1 subunit around 453 to 538 that interact with the ACE are 99% conserved among the variants of SARS-CoV-2 [106]. Their study further identified conserved common neutralizing epitopes on the SARS-CoV-2 including YLTPGDSSSGWTAGAAAYYV (247-267 aa), TFKCYGVSPTKLNDL (376-390 aa) on S1 and LNEVAKNLNESLID-LQELGK (1186-1205 aa) on the S2 [106]. A recent immunoinformatic study predicted conserved and highly immunogenic CTL-induced epitopes on S1 VRFPNITNL (327-335 aa), and PYRVVVLSF (507 -515 aa) (Table 1), while the CTL-induced epitopes on S2 were identified to be VVFLHVTYV (1060-1068 aa) and GVVFLHVTY (1059-1067 aa) (Table 2) [107].…”
Section: Sars-cov-2 S Conserved Regions As a Potential Target For Vac...mentioning
confidence: 99%